Avian community composition and feeding guilds in the agricultural area of Padangsidimpuan City, North Sumatra, Indonesia - NURUL HUSNA SIREGAR; RIZKY AMELIA DONA SIREGAR; PERIMA SIMBOLON (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Siregar NH, Siregar RAD, Simbolon P. 2026. Avian community composition and feeding guilds in the agricultural area of Padangsidimpuan City, North Sumatra, Indonesia. Biodiversitas 27 (5): d270524. https://doi.org/10.13057/biodiv/d270524. Agricultural expansion has altered tropical landscapes and may influence bird communities. This study aimed to examine bird community composition, feeding guild structure, and conservation implications in agricultural areas of Padangsidimpuan City, North Sumatra, Indonesia. Data were collected from August to September 2025 using point count surveys at three sites selected based on dominant agricultural land use and environmental variation, particularly elevation and vegetation differences. Each site included five observation points spaced 200 m apart, totaling 45 observation events with three repeated surveys per point. A total of 907 individual birds were recorded, representing 60 species from 30 families. The highest species richness and diversity were recorded in Aek Najaji (diversity index: 2.87; richness index: 6.30), followed by Bonan Dolok and Lubuk Raya. Differences among sites indicate variation in species composition and abundance despite similar land-use types. Nine feeding guilds were identified, with insectivores representing the highest number of species (17 species), followed by frugivore-insectivores (13 species). Higher diversity observed at sites with more heterogeneous vegetation and topography suggests a potential association between habitat complexity and bird communities, although habitat variables were not quantitatively analyzed. These findings indicate that agricultural landscapes may contribute to supporting bird diversity. Management practices such as maintaining mixed garden systems, preserving natural vegetation, and retaining riparian elements may support the persistence of bird communities in agricultural landscapes.